Ensinar na escola do campos: desafios da prática docente em contexto ribeirinho - Santana, Genay Oliveira (Brasil, 2024)
This article has as its central idea to address the challenges faced by teachers in the reality of a riverside community in Parintins (AM). The subjects of the field have experiences and experiences that unite and generate knowledge loaded with singularities, where the land, forests, animals, ecosystems are considered and respected. The various educational realities reveal how the riverside schools lack a careful look and concrete measures to minimize the problems that permeate the pedagogical practices in these environments. In this way, authors such as Caldart (1997; 2012; 2024) Arroyo, Caldart, Molina (2011), Vasconcelos (2016; 2017) contributed with reflections and theoretical discussions on the subject. And, from a qualitative approach and a research work directly in the community, we dialogue with teachers of a riverside school through semi-open interview, seeking to understand and achieve the objectives outlined. Teaching in riverside schools is challenging. The research presents results that confirm the need for improvements in working conditions that educators face, given the singularities and forms of riverside populations, their subjects, cultures and specificities.